2005
DOI: 10.1152/ajplung.00128.2005
|View full text |Cite
|
Sign up to set email alerts
|

Length oscillation induces force potentiation in infant guinea pig airway smooth muscle

Abstract: -Deep inspiration counteracts bronchospasm in normal subjects but triggers further bronchoconstriction in hyperresponsive airways. Although the exact mechanisms for this contrary response by normal and hyperresponsive airways are unclear, it has been suggested that the phenomenon is related to changes in force-generating ability of airway smooth muscle after mechanical oscillation. It is known that healthy immature airways of both humans and animals exhibit hyperresponsiveness. We hypothesize that the profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 36 publications
2
30
3
Order By: Relevance
“…A higher level of a-SM-actin expression may indicate more actin monomers that can form longer actin filaments by polymerization in the asthmatic inflammatory environment. 33 Smooth muscle cells with longer actin filaments show a more elastic behavior, which can generate force even after being stretched, 34,35 and may therefore increase airway hyperresponsiveness. Desmin, on the other hand, is an intermediate filament, present in dense bodies, and stabilizes the contractile units and participates in stress transmission between contractile units and anchorage sites linking to the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…A higher level of a-SM-actin expression may indicate more actin monomers that can form longer actin filaments by polymerization in the asthmatic inflammatory environment. 33 Smooth muscle cells with longer actin filaments show a more elastic behavior, which can generate force even after being stretched, 34,35 and may therefore increase airway hyperresponsiveness. Desmin, on the other hand, is an intermediate filament, present in dense bodies, and stabilizes the contractile units and participates in stress transmission between contractile units and anchorage sites linking to the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…ASM becomes progressively less compliant but more sensitive to acetylcholine with maturation in sheep [212], while the shortening velocity and passive stiffness of guinea pig trachealis both increase in the first 3 weeks of life and then decline [213,214]. More significantly, the force-generating ability of ASM is potentiated by stretch in infant guinea pigs but not in adult animals [215], and appears to be related to maturational changes in the release of prostanoids [216]. These findings may have relevance to the observations of WEIST et al [206], who showed that airway reactivity in healthy infants is not only greater than that in healthy adults, but is also insensitive to deep inspiration, similar to the situation in asthmatic adults [18] and in passively sensitised human bronchi [217].…”
Section: Effects Of Chronic Lung-volume Alteration and Smooth Muscle mentioning
confidence: 99%
“…In this respect, the guinea pig is unique because its airway innervation is very similar to that of humans (Wang et al, 2005). Moreover, guinea pigs are widely used in pulmonary pharmacology because their responses to various mediators and drugs are more similar to that of the human airway (Ressmeyer et al, 2006).…”
mentioning
confidence: 99%